Initial response analysis of Robot-Based Intervention Program (RBIP) for children with autism using humanoid robot NAO / Luthffi Idzhar Ismail - Ismail, Luthffi Idzhar (2013)
In recent decade, robotics has become very significant in assisting the children with autism in the areas like social interaction, emotion recognition, interactive plays, joint attention and special education. Autism is a brain developmental disorder that affects an individual’s social interaction, communication impairments and restricted stereotyped behaviour. Currently, research on the robotics for autism children shows suggestive finding in helping them to improve their quality of lifestyle and adapting themselves to their surroundings. Motivated by these emerging factors, the main objective of this research is to design and propose an interactive robot-based intervention modules using humanoid robot and analyze the initial response of autism children when they are expose to the module in an experimental program called Robot-based Intervention Program (RBIP). The methodology and outcome of this research are outlined in several stages that will be described in details in the Chapter 3. The initial response analysis is being done using modified Behaviour Score Sheet with reference to the Gilliam Autism Rating Scale (GARS) second edition. Based on the experiments that has been conducted in the RBIP and normal classroom, the results shows that 83.3% of the participated children response positively to the interaction in RBIP while another 16.7% response very good in normal classroom interaction for their stereotyped behaviour subscale and communications subscale. On the other hand, only 50% of the participated children with autism response positively in the social interaction subscale in the RBIP while 41.7% response optimistically to the normal classroom interaction while the remaining of 8.3% is not being able to be evaluated since the participants did not cooperate during the interaction in both RBIP and normal classroom experimental setting. Overall, most of the children are positively respond in RBIP which indicate that the robotic intervention program is an effective intervention program for them in improving their impairment in irregular repetitive stereotyped behaviour, communication skills and social interaction skills. Lower score in the three-subscale evaluation of Behaviour Score Sheet during RBIP is indicated that they exhibit less autism characteristic during RBIP compared to the normal classroom interaction.